Occupational exposure to glyphosate and risk of lymphoma:results of an Italian multicenter case-control study - Federico Meloni; Giannina Satta; Marina Padoan; Andrea Montagna; Ilaria Pilia; Alessandra Argiolas; Sara Piro; Corrado Magnani; Angela Gambelunghe; Giacomo Muzi; Giovanni Maria Ferri; Luigi Vimercati; et al. (Environmental Health, 2021)
Abstract Background The International Agency for Research on Cancer (IARC) recently classified glyphosate, the most used herbicide worldwide, as a probable human carcinogen. We inquired into the association between occupational exposure to glyphosate and risk of lymphoma subtypes in a multicenter case-control study conducted in Italy. Methods The Italian Gene-Environment Interactions in Lymphoma Etiology (ItGxE) study took place in 2011–17 in six Italian centres. Overall, 867 incident lymphoma cases and 774 controls participated in the study. Based on detailed questionnaire information, occupational experts classified duration, confidence, frequency, and intensity of exposure to glyphosate for each study subject. Using unconditional regression analysis, we modelled risk of major lymphoma subtypes associated with exposure to glyphosate adjusted by age, gender, education, and study centre. Results Very few study subjects (2.2%) were classified as ever exposed to glyphosate. Risk of follicular lymphoma (FL) was elevated 7-fold in subjects classified as ever exposed to glyphosate with medium-high confidence, 4.5-fold in association with medium-high cumulative exposure level, 12-fold with medium-high exposure intensity, and 6-fold with exposure for 10 days or more per year. Significant upward trends were detected with all the exposure metrics, but duration. The overall p-value for an upward trend with four independent metrics was 1.88 × 10− 4. There was no association with risk of lymphoma (any subtype), Non Hodgkin Lymphoma, B-cell lymphoma, or the major lymphoma subtypes other than FL. Conclusions Our findings provide limited support to the IARC decision to classify glyphosate as Group 2A human carcinogen.